2021
DOI: 10.3390/ijerph18041864
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Low Blood Pressure and Attention-Deficit Hyperactivity Disorder (ADHD) Observed in Children/Adolescents Does Not Persist into Young Adulthood. A Population-Based Ten-Year Follow-Up Study

Abstract: Background: Attention-deficit hyperactivity disorder (ADHD) is one of the most common behavioral disorders in childhood and adolescence associated with relevant psychosocial impairments. The basic pathophysiology of ADHD may be related, at least partly, to a deficit in autonomic arousal processes, which not only influence core symptoms of the disorder, but may also lead to blood pressure (BP) deviations due to altered arousal regulation. Objectives: This study examined long-term changes in BP in children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…Besides, studies treating learning difficulties and ADHD as end-points may miss mild early-onset cognitive decline that does not produce significant learning difficulties ( 38 ). The executive deficits can be associated with attentional problems in children with AH, however, children with ADHD seem to present lower levels of BP ( 46 ), so the deficits related to AH could be independent from the ADHD symptomatology. Recently, it has also been shown that uric acid levels alongside high BP are associated with worse executive functions ( 36 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Besides, studies treating learning difficulties and ADHD as end-points may miss mild early-onset cognitive decline that does not produce significant learning difficulties ( 38 ). The executive deficits can be associated with attentional problems in children with AH, however, children with ADHD seem to present lower levels of BP ( 46 ), so the deficits related to AH could be independent from the ADHD symptomatology. Recently, it has also been shown that uric acid levels alongside high BP are associated with worse executive functions ( 36 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Our study further elaborates recent studies on younger populations which found that untreated ADHD is associated with low blood pressure in late adolescence 24 but that this finding does not persist into young adulthood. 25 This would suggest the need to examine mechanisms that lead to the increase in blood pressure through adulthood for individuals with ADHD and the need for caution in interpreting any findings from more recent cohorts that focus on examining the long-term effects of medication for ADHD on blood pressure.…”
Section: Associations With Blood Pressurementioning
confidence: 99%
“…Однак ці відмінності не зберігалися після 10-річного спостереження. Автори роблять висновки, що саме ці зміни від підліткового до раннього дорослого віку можуть відображати зміни в стані вегетативного збудження, модулюючи патофізіологію СДУГ та його вплив на рівень АТ у дітей [30].…”
Section: вступunclassified